The protective effect and antitumor activity of Aconiti Lateralis Radix Praeparata (Fuzi) polysaccharide on cyclophosphamide-induced immunosuppression in H22 tumor-bearing mice - Hu, Qi; Liu, Yu; Yu, Ji; Yang, Xin; Yang, Ming; He, Yanan; Han, Li; Zhang, Dingkun (Frontiers in Pharmacology, 2023)
Background:Aconiti Lateralis Radix Praeparata, also known as Fuzi in Chinese, has been used in Traditional Chinese Medicine for more than 2,000 years. In recent years, some traditional herbal compounds containing Fuzi have achieved positive clinical results in tumor treatment. And the polysaccharide isolated from Fuzi has attracted much attention as a potential immunomodulator. However, its immunomodulatory mechanism remains to be further studied. Aim of the study. Fuzi neutral polysaccharide (FNPS) and cyclophosphamide (CTX) were combined to treat Hepatoma 22 (H22) tumor-bearing mice, and its mechanism of ameliorating immunosuppression caused by CTX was studied. Methods: FNPS was isolated and purified. The molecular weight, functional groups, monosaccharide composition, and apparent morphology were characterized by gel permeation chromatography, Fourier transform infrared spectrometer, ion chromatography and scanning electron microscope, respectively. Through the analysis of tumor, immune organs, and serum cytokine levels of H22 tumor-bearing mice, the immunomodulatory effect and the protective effect on immunosuppressive mice induced by CTX was evaluated. And the immunomodulatory activity of FNPS was further verified by macrophage functional experiments. Results: FNPS was composed of rhamnose, arabinose, galactose, glucose, and mannose in a molar ratio of 0.008:0.017:0.018:0.908:0.048. Its molecular weight was 94 kDa. In vivo experiments showed that 200 mg mL−1 FNPS could alleviate the suppression of immune organs and immune cells caused by CTX treatment, enhance the antitumor effect of CTX, increase the serum levels of Th1 immune-related pro-inflammatory cytokines (IL-1β and IL-6), and decrease Th2 immune-related anti-inflammatory cytokine (IL-10) and tumor-related pro-inflammatory cytokine (TNF-α) in the chemotherapy mice. Functional experiments revealed that 25 μg mL−1 FNPS could promote phagocytosis and proliferation of macrophages. When the concentration reached 50 μg mL−1, it enhanced the migration activity. Conclusion: FNPS has the potential to alleviate the immunosuppressive effect of CTX by activating immune cells and promoting inflammation. It could be used as a potential auxiliary medication for liver cancer treatment.